2009
DOI: 10.1002/lary.20585
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of septal deviation effects on nasal air flow: A computational fluid dynamics model

Abstract: This CFD study provides detailed information of the aerodynamic effects of nasal septal deviation on nasal airflow patterns and their associated physiological functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 31 publications
5
131
1
Order By: Relevance
“…Similar results of flow partition were noted between the PIV method and CFD method. Rapid wall pressure drop and highly localized wall shear stress were noted in one of the patients with nasal obstruction in our study as like the result of other report [7]. The consistency of the result should be evaluated for more nasal cavity models.…”
Section: Wall Shear Stresssupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results of flow partition were noted between the PIV method and CFD method. Rapid wall pressure drop and highly localized wall shear stress were noted in one of the patients with nasal obstruction in our study as like the result of other report [7]. The consistency of the result should be evaluated for more nasal cavity models.…”
Section: Wall Shear Stresssupporting
confidence: 72%
“…On the DSN, CFD simulation was used to investigate the aerodynamic change after virtual septoplasty and partial turbinectomy. [6] The aerodynamic effects of DSN was evaluated using CFD method and changed patterns of inspiratory airflow, wall shear stress and total negative pressure through the nasal cavity were reported for one patient with DSN [7]. With severe asymmetric nasal cavities due to DSN, some patients experience pain or discomfort but the others don't.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of sinonasal papilloma is unknown and seems different from that of rhinosinusitis, which is mainly caused by drainage problems. Recent studies have demonstrated the effect of septal deviation on airflow using computational fluid dynamics (Chen et al 2009;Orlandi 2010). The concave side shows increased velocities and turbulence in the middle meatal area.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was no correlation in female patients ( p = 0.842). meatal area (Chen et al 2009). The traumatic effects of the wall shear stress caused by the high velocity of airflow in the concave side might result in the high incidence of maxillary fungus ball.…”
Section: Abnormalitymentioning
confidence: 99%